Meritokrasi Birokrasi, Kesejahteraan Pegawai, dan Prinsip Syariah: Studi Kasus IAIN Pontianak - Rahimi, Muhamad; Ruslan, Ismail; Sumin, Sumin (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
This study evaluates the impact of Ministerial Regulation No. 17 of 2021 on the transition from structural to functional positions and its implications for the welfare of civil servants at IAIN Pontianak. As part of Indonesia's national bureaucratic reform aimed at fostering meritocracy and performance-based governance, the policy's effects were examined using a mixed-methods approach and exploratory sequential design. Data were collected through in-depth interviews and online surveys involving 14 affected civil servants. Findings reveal that the policy positively influenced employees' financial well-being through increased allowances, clarified job roles, and improved work motivation. Despite transitional challenges such as workload adjustments, most respondents felt more valued and productive. The study concludes that the policy enhances both financial and psychosocial dimensions of employee welfare. The implication highlights the importance of justice and Islamic ethical principles in public policy, especially within religious institutions.